CEAGESP in the far west of the state of São Paulo as an integral agent of the horticultural productive spatial circuit - Dionisio , Larissa Oliveira; Hespanhol, Antonio Nivaldo (Seven Editora, 2024)
The Companhia de Entreposto e Armazéns Gerais de São Paulo (CEAGESP) was created in 1969, currently has the largest public network of warehouses in the State of São Paulo and a complex of 13 wholesale units, being a mixed economy company linked to the Ministry of Agriculture, Livestock and Supply (MAPA). The objective of this work is to analyze the three units of the Companhia de Entreposto e Armazéns Gerais de São Paulo (CEAGESP), namely: Araçatuba, Presidente Prudente and São José do Rio Preto and their spatial circuit of fruit and vegetable production. The analyses were undertaken based on the notion of spatial circuits of production, developed by Milton Santos in 1986. To achieve the objectives of the investigation, documentary and bibliographic research was carried out on technical objects, supply centers and horticultural productive spatial circuits and data collection in publications of the National Supply Company (CONAB), in addition to CEAGESP itself. DOI:https://doi.org/10.56238/sevened2024.023-027